Mapping A Contextualized Southern Africa's Innovation Ecosystem: The Emerging Role of Higher Education in Promoting Inclusive Innovation and Rural Industrialization - Vhonani O Netshandama; Simbarashe Kativhu; Tumelo Sekgobela (International Journal of Rural and Regional Development, 2026)
Higher education institutions (HEIs) are increasingly recognized as strategic actors in shaping innovation ecosystems that can respond to persistent socio-economic inequalities in the Global South. In Southern Africa, where rural underdevelopment, youth unemployment, weak industrial bases, and uneven innovation capacities remain pressing concerns, universities are under growing pressure to move beyond their traditional teaching and research mandates and contribute more directly to inclusive development. This paper examines the emerging role of HEIs in promoting inclusive innovation and rural industrialization within a contextualized Southern African innovation ecosystem. Drawing on a qualitative mapping exercise conducted by the University of Venda’s Directorate for Community Engagement, Entrepreneurship, Inclusive Innovation and Commercialization, the study integrates institutional cases, policy documents, and regional literature with global theoretical perspectives, including Mode 2/3 knowledge production, the quadruple and quintuple helix models, and the scholarship of engagement. The findings show that HEIs have significant potential to function as brokers, convenors, and place-based anchors that facilitate co-creation, entrepreneurship, inclusive commercialization, and rural value-chain development. Evidence from selected Southern African institutions illustrates emerging practices such as innovation hubs, community engagement platforms, agribusiness support and socially oriented incubation. However, these contributions remain constrained by fragmented policy environments, resource limitations, urban-biased commercialization pathways, weak regional knowledge flows and academic incentive systems that continue to privilege conventional scholarly outputs over social impact. The paper argues that a more context-sensitive and development-oriented innovation ecosystem is required, one that embeds engagement, indigenous knowledge, and inclusive commercialization within the core mission of universities. It concludes that HEIs can play a transformative role in advancing equitable innovation and rural industrialization in Southern Africa, provided that institutional reforms and supportive policy frameworks are aligned to local realities and developmental priorities.
Keywords: commercialization; entrepreneurship; higher education; inclusive innovation